Terre objective: essais d'éthique environnementale - book summary - Rolston, Holmes, 1932-2025, author; Madelin, Pierre, author; Afeissa, Hicham-Stéphane, author; Éditions Dehors, publisher (Colorado State University. Libraries, 2018)
There are eight essays, featuring Rolston's arguments about objective value on natural landscapes, and how this is needed, beyond resource values for people, in environmental ethics.
Objective Earth: environmental ethics essays - book summary
Translated by Pierre Madelin and Hicham-Stéphane Afeissa.